Spirometric Values of Healthy School Children in Three Rural Schools of Bangladesh (Bangladesh Journal of Child Health, 2024)
Background: The prevalence of asthma in Bangladesh is about 7%. The spirometric values in healthy children were obtained in a single urban school more than a decade ago. No rural data is available till date. The objective of this study is to determine the spirometric values of healthy school going children in three rural schools of Bangladesh.Materials and Methods: This cross-sectional study was carried out from July 2019 to June 2020 among 300 healthy children among both boys and girls aged 11 to 15 years in three rural schools. Among 350 approached students 332 students responded to the study, 18 students did not meet inclusion criteria and 14 students could not follow spirometry procedure. Informed written consent was taken from guardians. History regarding socio-demographic profile, passive smoking, concurrent or past respiratory illness and medication were taken and weight, height and BMI were measured of the children. Spirometry was done with spirometer and reports were generated by software installed in a laptop.Results: Boys showed higher FVC, FEV1 and PEFR but lower FEV1/FVC ratio than those of girls. Regression equations for lung function values were determined for boys and girls considering height as independent variable.Conclusions: Spirometric indices were higher in boys than those of girls and they tended to increase with height, except FEV1/FVC ratio that was higher in girls with a negative correlation with height.BANGLADESH J CHILD HEALTH 2023; VOL 47 (1) : 17-23